2013
DOI: 10.1002/nau.22469
|View full text |Cite
|
Sign up to set email alerts
|

Development of two electronic bladder diaries: A patient and healthcare professionals pilot study

Abstract: This proposed e-diary with its intuitive interface has overcome previous deficiencies in electronic diaries with most patients finding the format user-friendly. Electronic reports make analysis and interpretation by HP quicker and more accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Symptoms which showed lower agreements were the presence of nocturia or nocturnal polyuria, which is something that has already been showed by other authors, who found greater variability in the nocturnal events . A possible explanation is that patients might find some difficulties in recording voids at night with an electronic diary as this could require a degree of wakefulness which could interfere with the sleep cycle …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Symptoms which showed lower agreements were the presence of nocturia or nocturnal polyuria, which is something that has already been showed by other authors, who found greater variability in the nocturnal events . A possible explanation is that patients might find some difficulties in recording voids at night with an electronic diary as this could require a degree of wakefulness which could interfere with the sleep cycle …”
Section: Discussionmentioning
confidence: 74%
“…However, recording the events at the time they occur is essential to avoid recall bias, as events postponed might be forgotten afterwards. Although clinicians’ preferences were not assessed in this study, other studies show that they may prefer electronic diaries rather than paper formats due to the time saving or the comprehensiveness of the report …”
Section: Discussionmentioning
confidence: 99%
“…Further, the device analyzed the data entered by the patients in real time. According to a study comparing the efficacy between an paper diary read electronically and an e-diary made with a touch screen device similar to a smartphone, patients preferred the e-diary [42]. As people are accustomed to mobile devices, electronic VDs are expected to become more popular.…”
Section: Electronic Voiding Diariesmentioning
confidence: 99%
“…First eBDs were cumbersome devices with complex algorithms that made them difficult to use . However, recent pilot studies assessing new eBD devices show that eBD have advantages for both patients and clinicians . On the one hand, they help patients facilitating intuitive data entry which may improve compliance.…”
Section: Introductionmentioning
confidence: 99%